Interfaith Marriages in Brambaken Village: Legal Ambiguities and Sociocultural Dynamics in Biak Numfor Regency - Wutwensa, Bruri Marwano (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2023)
This research examines interfaith marriages in Indonesia, with a specific focus on Brambaken Village, Samofa District, Biak Numfor Regency. Marriage is regarded as a sacred bond that must adhere to the religious laws of each party, as stipulated in Article 2, paragraph (1) of Law No. 16 of 2019, in conjunction with Law No. 1 of 1974 concerning Marriage. Despite this, interfaith marriages continue to occur in society, even though they are not explicitly regulated by this law, leading to legal uncertainty. The objective of this research is to assess the validity of interfaith marriages under current legal frameworks and to identify the factors that contribute to the prevalence of interfaith marriages in the Biak Numfor Regency. Employing an empirical juridical approach, this study utilizes primary data from interviews and secondary data from literature reviews. The findings indicate that interfaith marriages persist as a social phenomenon despite legal ambiguity, driven by complex social and cultural factors such as the dominance of syncretic cultural practices, secularism, religious formalism, disproportionate tolerance, and the presence of premarital children.